Saponins Based on Medicinal and Edible Homologous Plants: Biological Activity, Delivery Systems and Its Application in Healthy Foods - Siwen Chen; Ying Zhou; Huiliang Li; Lijun You; Sandra Pedisić; Ping Shao (Food Bioengineering)
ABSTRACT Medicinal and edible homologous (MEHs) plants are valuable in medicine and food science as edible plants. Saponins, one of the major chemical components isolated from MEHs plants, have significant antioxidant, anti‐inflammatory, antibacterial, and antiviral biological activities. This paper provides an overview of the basic structure, properties, and bioactivity of saponins, the development of novel delivery systems for their enhanced bioavailability, and their applications in various fields. It also highlights the innovations and challenges of current trends in saponin research and provides a basis for the development of a safe and effective natural active ingredient based on MEHs plants. Through comprehensive analysis, this paper aims to provide a theoretical basis and technical support for further research and application of saponins in food science.